Additive manufacturing of copper/diamond composites for thermal management applications. (April 2020) - Constantin, Loic; Fan, Lisha; Pontoreau, Mael; Wang, Fei; Cui, Bai; Battaglia, Jean-Luc; Silvain, Jean-François; Lu, Yong Feng
Abstract: Copper (Cu)/diamond (D) composites have excellent thermal properties but are hard to manufacture with conventional methods. Additive manufacturing (AM) can overcome this issue because of its high degree of freedom to fabricate complex designs. In this letter, we demonstrate the laser directed energy deposition of Cu/D composites. D particles were coated with graded TiO2 -TiC interphase to enhance its wettability with molten Cu. A relatively dense Cu/25 vol% coated-D composite was printed (96%) at an energy density of 1200 J/mm 3 (power = 900 W, scan = 12.7 mm/s) with high thermal conductivity (330 W/m.K), and no graphitization of the D.